A multifaceted approach to improving motor vehicle restraint compliance. Issue 2 (1st June 2000) - Hanfling, Marcus J; Mangus, Lorna G; Gill, Anne C; Bailey, Rick
Abstract : Objectives —To increase proper use of seat belts and car seats, thereby reducing morbidity and mortality from motor vehicle collisions. Setting —The Vehicle Injury Prevention program community intervention was implemented in Houston, Texas. Effectiveness data are limited to "target area one", an impoverished neighborhood in northeast Harris County. Methods —This multifaceted public health education campaign brought together six segments of the community: education, health, government, law enforcement, private industry, and the media, to improve restraint use. It was evaluated by observation of proper restraint use before and nine months after implementation. Trained, independent observers made observations of occupants in the target area and at two comparison sites. Pre-post differences in restraint compliance were calculated by a standard binomial proportion test. Results —Motorists in target area one significantly improved their restraint use by 15% (p<0.05) from 39% pre-intervention to 54% post-intervention, whereas use in the comparison neighborhoods remained unchanged. Conclusions —Implementation of a public health education program, combined with economic incentives to increase vehicle restraint use, can be successful with multifaceted community support.